Jogos sérios em ambiente virtual para ensino-aprendizagem na saúde - Cristiano Alves dos Santos; Valtuir Duarte Souza-Junior; Flávio Ferreira Lanza; Allan Jonny Lacerda; Beatriz Maria Jorge; Isabel Amélia Costa Mendes (Universidade Federal do Ceará, 2017)
Objective: to identify the evolution in the use of serious games in virtual environments for health teaching and learning in the literature. Methods: integrative review with searches in the databases: Web of Science, National Library of Medicine, Cumulative Index to Nursing and Allied Health Literature. Results: in total, 82,779 articles were identified, 13 of which were fully read. Serious games are cheaper than simulated surgical procedures, easy to access and appropriate for the development of surgical skills and the training of patients, skills, clinical reasoning and decision taking. Conclusion: serious games have been developed through the elaboration of software and specific interactivity tools, mainly focused on skills development; using internet components, especially in Medicine and Nursing; and use peripherals of the computers in the teaching-learning strategies to encourage clinical reasoning and decision making.